Analisis Kesulitan Siswa dalam Pemahaman Materi IPS Terpadu di SMP Negeri 1 Sidikalang - Dame Martina; Christin Eva; Tumiar Sidauruk; Dini Afrilia; Putri Roito; Muhammad Alfi; Wafiq Ariska; Vinny Natasya; Ryan Pramana; Grace Holyvia (Universitas Palangka Raya, 2024)
IPS can be interpreted as a study or study of society. Difficulties in understanding social studies material can be caused by various factors, such as the complexity of the content, less effective teaching methods, and a lack of connection between the material and students' daily lives. These factors can hinder students' learning process and affect their overall learning outcomes. The method used in this research is a questionnaire which is a data collection method carried out by giving a set of questions or written statements to respondents to answer. The data collection techniques used are primary data and secondary data, where primary data is data directly obtained from respondents while secondary data is data obtained from sources relevant to the research topic, such as books, articles, theses, etc. The results of this research show that the interest of students at SMP Negeri 1 Sidikalang in International Trade material varies, with 50% very interested but 26.7% feeling less interested. The main obstacle comes from the teacher's delivery which is considered less interesting and material which is considered irrelevant to everyday life. Although many students find assignments and evaluations helpful, there is an urgent need for innovation in learning methods to make them more interactive and relevant. Based on the results of a survey conducted via Google Form on 10 respondents from students at SMP Negeri 1 Sidikalang, it appears that students face various obstacles in understanding and being interested in international trade material.